Halštatske nekropole Dolenjske = Die hallstattzeitlichen Nekropolen in Dolenjsko - Dular, Janez (Opera Instituti Archaeologici Sloveniae, 2003)
This publication presents fifty-four Hallstatt necropolises from central Slovenia, which are crucial to the course of researching the settlement and social structures of the Early Iron Age. Topographic sources are proffered as well as all the excavated materials, among which are also unique specimens.The book is divided into three parts. The first section extends a review of the history of excavations of Hallstatt tumuli, from the very onset and all through to WWI. It is a comprehensive study of the history of archaeology in Slovenia, posing the development of museology, the heritage protection profession and the professional and scientific efforts of the then investigators. Numerous illustrations of yet unpublished documents, preserved mainly in foreign museums and archives, are incorporated in the text.The second section is dedicated to the issue of chronology and the cultural- historical evaluation of Hallstatt necropolises in the Dolenjska region, which regarding their richness easily compare with the most important of necropolises in neighboring countries. It is precisely the tumulus necropolises from the Dolenjska region that form the foundations for the concept of the southeastern Alpine Hallstatt culture, which during the first millennium BC represented one of the most developed cultures in Europe.